Challenges and barriers of blended learning among Asian health sciences students: a pilot study - Saber, Huda (Penerbit Universiti Sains Malaysia, 2022)
This study explored the perception, engagement, learning experiences, as well as challenges and barriers in blended learning (BL) or the combination of multiple delivery methods designed to complement educators and learners, of students in the health sciences courses in Universiti Putra Malaysia (UPM). A qualitative approach was performed using focus group discussions (FGDs). Eight medical, eight nursing and seven biomedical students were selected according to a set of criteria. Three FGDs were conducted using a semi-structured topic guide. Data were collected through audiorecordings and transcriptions. Data coding and analysis were performed using inductive content approach. Three topic highlights were developed from the analysis. Students referred to BL as an online learning platform which does not involve lectures nor lecturers. They agreed that BL allows self-directed and collaborative learning, besides it fits their learning styles. Some of them highlighted some limitations of BL when it comes to slow-learners, student-lecturer engagement and the existing infrastructure. The students also shared their good and bad experiences regarding BL, as well as feedbacks to help improve its implementation. There are a mix of positive and negative perceptions and experiences highlighted in this study. The integration of BL to the existing traditional learning style is challenging. Therefore, by examining the strengths and weaknesses of BL that have been identified in this study, it is hoped that the students’ learning experiences could be made better. Future studies could investigate more on BL implementation in larger student population to ensure its beneficial aspects towards enhancing students’ learning progress.